Prevalence of serum MOG antibody and AQP4 antibody in optic neuritis after SARS-CoV-2 infection - Sun, Chuan-bin (Frontiers in Immunology, 2023)
Purpose: To evaluate the prevalence of serum myelin oligodendrocyte glycoprotein antibody (MOG-Ab) and aquaporin-4 antibody (AQP-4 Ab) in optic neuritis (ON) patients after SARS-CoV-2 infection by cell-based indirect immunofluorescence assay (CBA).In this prospective case series study, thirty-five patients clinically diagnosed as ON and laboratory confirmed SARS-CoV-2 infection from December 8, 2022 to February 8, 2023 were included. All patients' clinical and laboratory data were collected and analyzed.Results: Mean age of 35 patients (46 eyes) was 38.2 years (ranged from 6 to 69 years), female was 17 cases. Thirty-three and two cases showed positive SARS-CoV-2 RNA test results before or shortly after ON onset, respectively. ON occurred unilaterally in 24 cases and bilaterally in 11 cases. Ophthalmic examination revealed swollen optic in 37 eyes, normal optic disc in 6 eyes, temporally or wholly paled optic disc in 3 eyes. CBA revealed seropositive MOG-Ab in 10 cases, and AQP4-Ab in 2 cases respectively, among whom, two AQP4-Ab seropositive and one MOG-Ab seropositive case had a past medical history of ON. Most ON patients showed a rapid and dramatic response to pulse steroid therapy.The median of BCVA at onset and at last follow-up was 20/500 (ranged from light perception to 20/20) and 20/67 (ranged from counting fingers to 20/20), respectively.Conclusions: Serum MOG-Ab and AQP-4 Ab were detected in 28.6% (10/35) and 5.7%(2/35) ON cases after SARS-CoV-2 infection. SARS-CoV-2 infection may trigger an onset or a relapse of ON, as well as the production of MOG-Ab.